METHODS OF MANAGING CHANGES IN EDUCATIONAL INSTITUTIONS OF UKRAINE DURING THE CRISIS (COVID-19, WAR): STRATEGIES FOR ADAPTATION AND ENSURING CONTINUITY OF LEARNING - Blikhar, Viacheslav; Hurkovskyi, Dmytro (Socio-economic relations in the digital society, 2025)
The article explores the methods of change management implemented in Ukrainian educational institutions during unprecedented crises: the COVID-19 pandemic and full-scale war. The author substantiates the relevance of the studied issues within the framework of both the urgent need to respond quickly to new challenges and threats and to create conditions for lifelong learning by supporting the provision of educational services in conditions of limited access to full-fledged education and taking into account the direct effect of the legal regime of martial law in Ukraine. Based on a comprehensive review of the current literature and case studies, the paper analyzes the adaptation strategies that have been used to ensure continuity of learning and build resilience. The key findings highlight the rapid digital transformation, the creation of physical security measures, the integration of broad psychosocial support, as well as the dynamic adaptation of curricula and teaching methods, which will require all stakeholders to rapidly mobilize technical and state-of-the-art educational opportunities. The high importance of international cooperation in supporting the educational landscape is emphasized. Applying established models of change management (ADKAR, Kotter, Levine) to the Ukrainian context, this article emphasizes the unique factors of sustainability, offering practical recommendations for political and educational actors facing complex, protracted crises. In this context, it is necessary to clearly take into account the possibility of psychological and pedagogical support for both higher education students and research and teaching staff (including pedagogical and scientific workers), since crisis challenges lead to constant stress, uncertainty, doubts, and, therefore, “distance relations” provoke non-compliance with the conditions for the provision of educational services. Based on the study, the understanding of crisis management in education has been further developed, emphasizing the interaction of technological, pedagogical and human-centred approaches in ensuring the smooth functioning of educational systems under extreme pressure.
Keywords: change management; educational institutions; crisis; COVID-19; war; adaptation; learning continuity; digital transformation; psychosocial support; Ukraine